APPLICATION OF THE PRINCIPLES OF ADAPTIVE ARCHITECTURE IN REVITALIZATION OF SACRED BUILDINGS, WHICH HAVE LOST THEIR SIGNIFICANCE - Kiuntsli, Р.; Stepaniuk, А. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
Adaptive architecture includes the design and construction, as well as the reconstruction and renovation of public, sacred and residential buildings, which have the ability to change their architectural planning characteristics in accordance with changes in operating conditions. These objects can change the planning structure, interior space, shape in accordance with the requirements of the new needs of the restored space. The term «Adaptive Architecture» was proposed by Nicolas Negroponte in the late 1960s, when spatial design problems began to be viewed with the use of cybernetics. In the developed countries of Europe and America, where society is developing based on technical progress, the attitude to architectural buildings that have lost their significance (abandoned but not operated by the owner) is more pragmatic. The prevailing view is that every building should serve human needs. Abandoned buildings and structures of factories, cinemas and theaters, barracks and bunkers are being revitalized (restored). All of them are updated to meet the requirements and needs of new customers: housing, hostels, warehouses, shopping malls and more. Today, the process of changing for the purpose of revitalization has affected sacred buildings, which have lost their purposes. Many religious communities in America and Europe are losing the capability to maintain their temples for different reasons- from the loss of interest in religious rites to the migration of the population and the reduction of believers of a particular denomination. In this case, the process of restoring sacred buildings that have lost their significance and adapting their space to new needs is seen the only way to preserve the historic buildings, improve existing ones and harmonize the environment. During the study and examining of a new type of architectural activity - the revitalization of sacred buildings that have lost their significance, the authors propose to apply the principles of adaptive architecture to solve this problem. Thus, in the project-proposal for the restoration of the Zhovkva synagogue, which lost its original functional significance, the authors propose to apply the principles and methods of adaptive architecture, namely the creation of a new, interspersed with existing mobile space, which can be transformed in space and time depending on the needs of the customer, along with leaving the constructive-spatial and architectural-artistic authenticity of the monument of sacred architecture.